Chemical Evaluation of the Nutrient Composition of Some Unconventional Animal Protein Sources - Ojewola, G.S.; Udom, S.F. (International Journal of Poultry Science, 2005)
A trial was conducted to assess the nutrient composition of some novel feed ingredients so as to enhance livestock development and human protein intake. Ten (10) unconventional protein sources which include fish, crayfish, frog, shrimps, crabs, squilla, toads and grasshopper were harvested, processed and analyzed for their proximate and mineral (macro) composition using internationally established procedures. The results showed that the samples had percent crude protein that ranged from 28.14 (crab) to 61.38 (local fish meal). Frog, toad, squilla, crayfish, pellonula and crab respectively recorded appreciable percent ether extract (EE) values of 9.14, 8.74, 7.21, 6.32, 6.26 and 6.02. The gross energy (kcal/g) value was highest for squilla (2.97), followed closely by crayfish (2.87), Pellonula (2.85), mudskipper (2.84) while the others were below 2.0kcal /g. The crab gave the highest percent ash content (39.11) while the local fish meal gave the least value (5.96). Local fishmeal had the highest percentage of calcium (2.56%) followed by Pellonula (1.94%) and Mudskipper (1.89%) while the others had values that were lower than 1%. Percent Phosphorus followed a similar trend as calcium with local fishmeal recording the highest value of 1.92%. The results of this study showed that all the samples possess an appreciable quantities of all the dietary elements tested for, which, more or less could make them partial or complete substitutes for the conventional feed sources.